2022
DOI: 10.9734/jamb/2022/v22i830481
|View full text |Cite
|
Sign up to set email alerts
|

The Production of Second-generation Bioethanol from Lignocellulosic Biomass using Two Strains of Sacharomyces cerevisiae

Abstract: Concerns about first generation bioethanol's impact on the food chain and biodiversity have shifted research to second generation (2G) bioethanol technologies. The 2G-bioethanol is made from lignocellulosic biomass, which is more sustainable and does not harm food security or the environment. This production process uses non-food crops, food crop residues, wood or food wastes, such as wood chips, skins, or pulp from fruit pressing. The present study examines the bioethanol production potential of three lignoce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…This shows that yeast strain has a considerable effect on the yield of ethanol. Adebayo et al [42] reported higher ethanol yield (20.13%; 201 g/L) from S. cerevisiae ATCC 36858 obtained from the Federal Institute of Industrial Research, Oshodi (FIIRO), Nigeria, than for Baker's yeast strain (8.53%; 85.3 g/L) in the fermentation of Zea mays cob cellulose-derived sugar. The highest yield from the palm wine yeast samples was observed for the 212 μm particle size sawdust feedstock with a value of 289.8 mL from 250 g of sawdust.…”
Section: Effect Of Particle Size and Yeast Strain On Product Yieldmentioning
confidence: 99%
“…This shows that yeast strain has a considerable effect on the yield of ethanol. Adebayo et al [42] reported higher ethanol yield (20.13%; 201 g/L) from S. cerevisiae ATCC 36858 obtained from the Federal Institute of Industrial Research, Oshodi (FIIRO), Nigeria, than for Baker's yeast strain (8.53%; 85.3 g/L) in the fermentation of Zea mays cob cellulose-derived sugar. The highest yield from the palm wine yeast samples was observed for the 212 μm particle size sawdust feedstock with a value of 289.8 mL from 250 g of sawdust.…”
Section: Effect Of Particle Size and Yeast Strain On Product Yieldmentioning
confidence: 99%